2021
DOI: 10.1186/s12887-021-02677-1
|View full text |Cite
|
Sign up to set email alerts
|

The association of dietary choline and betaine and anthropometric measurements among Iranian children: a cross-sectional study

Abstract: Background Previous studies have suggested that choline and betaine are associated with improved anthropometric measures including, BMI and waist circumference however, results are largely inconsistent and limited studies exist in children. Our objective was to investigate the relationship between dietary choline and betaine, and anthropometric measurements among Iranian children. Methods In this cross-sectional study, dietary information was colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
1
1
0
Order By: Relevance
“…Similar to our findings, in the study by Azad Bakht et al dietary betaine was significantly related to MAC (r = 0.093, P = 0.009) and obesity risk (P < 0.05), but there was no association between choline and anthropometric measurements [49]. in general population.…”
Section: Discussionsupporting
confidence: 91%
“…Similar to our findings, in the study by Azad Bakht et al dietary betaine was significantly related to MAC (r = 0.093, P = 0.009) and obesity risk (P < 0.05), but there was no association between choline and anthropometric measurements [49]. in general population.…”
Section: Discussionsupporting
confidence: 91%
“…We therefore included the total calorie intake as a major confounder in all the analyses to avoid misleading results. The beneficial effect of choline supplementation on body composition and body mass in human has been reported in previous studies 27,28 However, some studies have found no association of choline intake with obesity 29 Factors affecting different outcomes of these interventional studies on humans may include, for example, a period of supplementation and a daily dose of choline. By contrast, we reported that higher plasma choline was associated with higher BMI, body weight, body FM, and WC, which is the opposite to dietary choline intake.…”
Section: Discussionmentioning
confidence: 94%
“…Eight studies have reported choline intake in adults [ 17 , 18 , 24 , 27 , 28 , 54 , 66 ], one study measured choline intake in children [ 31 ], and four studies have recorded choline intake in pregnant women [ 13 , 33 – 35 ]. Among the twenty-one studies measuring choline intake in non-European countries, the majority (52%) were conducted in the USA [ 19 , 20 , 25 , 32 , 55 – 57 , 62 – 65 ], while the others were carried out in Palestine [ 58 ], South Africa [ 59 ], Australia [ 36 , 60 ], Mexico [ 23 ], Taiwan [ 16 ], Iran [ 22 , 29 ], Canada [ 21 , 61 ].…”
Section: Resultsmentioning
confidence: 99%
“…Choline intake was found to be above AI values only in infants and children aged 2–6 years [ 18 , 19 , 29 31 , 36 ].…”
Section: Resultsmentioning
confidence: 99%